Efektivitas Kelembagaan Awig-Awig dalam Mengelola Sumber Daya Perikanan Pantai di Kabupaten Lombok Timur - Nisa Ayunda; Aceng Hidayat; Zuzy Anna (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Some institution arrangements are developed to manage the fishery resources, one of which is a communitybased management. Over the past few years, this community has been believed to be one of the effective management. According to Schlager and Ostrom (1992); Imperial and Yandle (2005), this management was usually the adoption of local knowledge of communities around their resources. Awig Awig growing in East Lombok is one of a growing community based management in Indonesia in managing fishery resources. Based on this information, this research aimed to (1) diagnose the awig awig institution growing in East Lombok, (2) identify and analyze the external factors influencing the institution, and (3) evaluate awig awig institution linkages to sustainable coastal fisheries. This study used the approach of the Institutional Analysis and Development (IAD) framework and GS production surplus bioeconomy. The results showed that so far awig awig institution has not been able to overcome the pressure from the inside and from the outside in the form of appropriation externality, technology externality, and assignment problem, therefore, this caused the decline of fishery resources.